Comparative Study on FT and RV Type Pin-cycloid Planetary Reducer - Xuan Liang; Jiang Heng; Guan Tianmin; Lei Lei; Xie Chao (Jixie chuandong)
The FT pin-cycloid reducer and RV reducer are new type of pin-cycloid transmission reducer with closed two stage transmission. The both type of reducer has the advantages of more compact structure,high rigidity,low vibration,high efficiency of low speed operation zone and so on. The structure of the two is similar in transmission mode,and the transmission performance is greatly improved compared with the previous generations of reducer and the transmission efficiency is also greatly higher. The FT455-81 prototype and RV-160 E-81-B-B prototype are taken as examples to compare the performance,price and other aspects.The 3D model of the FT and RV reducers is built. Its transmission principle,transmission characteristics and structure are analyzed and compared. The advantages and disadvantages of RV reducer and FT reducer are expounded. The suitable for application of the two reducer is found.